Asuhan Kebidanan Continuity Of Care (Coc) pada Ny. R di Pmb Siwi Indriatni., S.TR.Keb - R., Arina Manasika P.; Cahyaningrum (Universitas Ngudi Waluyo, 2023)
Continuity of care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborn care and family planning services that connect the health needs of women in particular and the personal circumstances of each individual. The reason why women are at risk of complications during the prenatal, natal and postnatal periods is due to the lack of quality interaction between the midwife and the mother. The aim of this care is to provide midwifery care to pregnant, maternity, postpartum, neonate and family planning mothers at PMB Siwi Indriatni. This type of research is a case study. Guidelines for observation, interviews and documentation studies in the form of Midwifery Care format starting from pregnancy, childbirth, postpartum, newborn and family planning. The object of the Continuity of Care research will be given to Mrs. R, 35 years old, G1P0A0 starting from pregnancy, maternity, postpartum, newborn and family planning. The results of this research have been proven by the success of mothers giving birth in normal conditions and healthy babies. Based on the results of continuity of care midwifery care research that was carried out on Mrs. R hopes that clients can apply the counseling that has been given during their pregnancy so that one day if the mother is pregnant again, the mother will be educated to apply the knowledge that was given to the previous midwife in order to prevent complications and even death and it is hoped that the results of this research can educate midwives to apply Continuity of Care method to reduce maternal and infant mortality rates in Indonesia. Abstrak Continuity of care dalam kebidanan adalah serangkaian kegiatan pelayanan yang berkelanjutan dan menyeluruh mulai dari kehamilan, persalinan, nifas, pelayanan bayi baru lahir serta pelayanan keluarga berencana yang menghubungkan kebutuhan kesehatan perempuan khususnya dan keadaan pribadi setiap individu. Penyebab perempuan berisiko terjadinya komplikasi selama masa prenatal, natal dan post natal diakibatkan karena kurangnya kualitas interaksi antara bidan dengan ibu. Tujuan asuhan ini adalah untuk memberikan asuhan kebidanan pada ibu hamil, bersalin, nifas, neonatus dan KB di PMB Siwi Indriatni . Jenis penelitian ini adalah studi kasus (case study). Pedoman observasi, wawancara dan studi dokumentasi dalam bentuk format Asuhan Kebidanan mulai dari masa kehamilan, bersalin, nifas, bayi baru lahir dan KB. Objek penelitian asuhan Continuity of Care akan diberikan pada Ny. R umur 35 tahun G1P0A0 mulai dari kehamilan, bersalin, nifas, bayi baru lahir dan KB. Hasil penelitian ini telah di buktikan dengan berhasilnya ibu melahirkan dalam keadaan normal dan bayi sehat. Berdasarkan hasil penelitian asuhan kebidanan continuty of care yang telah dilakukan pada Ny. R diharapkan klien dapat menerapkan konseling yang telah diberikan selama kehamilanya sehingga suatu saat jika sang ibu hamil lagi, ibu sudah teredukasi untuk menerapkan ilmu yang telah diberikan kepada bidan sebelumnya agar dapat mencegah terjadinya komplikasi hingga kematian dan diharapkan hasil penelitian ini dapat mengedukasi para bidan untuk menerapkan metode Continuity of Care agar dapat menekan Angka Kematian Ibu dan Bayi di Indonesia.